Letters to the body: performative autographies in the formation of the body-artist-researcher (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This text explores the relationship between body and identity, based on Performative Education in dialogue with the methodology of (Auto)biographies. Through autographies as creative processes, we investigate how the presence of the body, or even the discursive body, contributes to the formation of the artist-researcher body. The study, carried out with Performing Arts students, examines the practice "Letters to the Body", revealing the discursive body as a significant material that re-signifies learning and identities in the construction of the subject and knowledge in artistic training.
Keywords: body; identity; performative education; autographs; artistic training